PERANCANGAN USULAN STRATEGI PENGELOLAAN PELANGGAN HOTEL MARCOPOLO JAKARTA - Ivan Sadanov Marpaung, Mauritz
Hotel Marcopolo Jakarta is a 3-star hotel located in Cikini, Central Jakarta. In 2022-2023, Hotel Marcopolo Jakarta recorded its highest occupancy rate since data was recorded in 2014 at 61,60% and 60,02%. This occupancy rate is higher than the average starred hotel occupancy rate in Jakarta, which is 53,88%, and Hotel Marcopolo Jakarta has never reached 60% occupancy rate between 2014-2021. This positive sign in occupancy rate was not followed by another important measure, which is the Average Room Rate (ARR). In contrast with the occupancy rate, Hotel Marcopolo Jakarta recorded its lowest ARR since 2014. This was due to the price reduction strategy used by the hotel to attract customer in order to increase its occupancy rate after the pandemic. In that case, Hotel Marcopolo Jakarta needs a strategy to increase profitability while retaining its occupancy rate and customers This research aimed to design a customer relationship management strategy to retain the price-sensitive customer of Hotel Marcopolo Jakarta and to increase the customer profitability